Attitudinal Militancy in A Canadian Postal Plant - Lewis, David Lloyd (McMaster University, 1995)
One tenet of labour process theory is the contention that, when confronted by degraded work, people will resist through militant behaviour or in other ways. However, that "resistance hypothesis" has been tested rarely. Canadian postal workers have manifested some considerable militancy, for instance through legal and wildcat strikes and through frequent recourse to the grievance mechanism. Too, their work has been subjected to technological change often pointed to as a prime example ofjob degradation. But not all aspects of postal work have been subjected to technological change. Thus, postal workers constitute a test ofthe "resistance hypothesis:" if degraded work provokes militancy, then ceteris paribus postal workers involved in automated work will be more militant than those who are not. In this study, a group of postal workers employed in "Cancity" in 1985-6 (N=152) were surveyed regarding their attitudes and experiences. Factor analytic techniques were used to construct a scale of attitudinal militancy, and hierarchical set analysis - summarised using dummy variable path coefficients - was used to examine the causal links between this outcome and logically prior factors, including job degradation, employment history, and achieved and ascribed statuses including sex. The results indicate that job degradation does have an impact on attitudinal militancy, but that this impact is modest at best, and weakens as other influences are taken into account.